2020
DOI: 10.3389/fcell.2020.592164
|View full text |Cite
|
Sign up to set email alerts
|

The Why of YY1: Mechanisms of Transcriptional Regulation by Yin Yang 1

Abstract: First described in 1991, Yin Yang 1 (YY1) is a transcription factor that is ubiquitously expressed throughout mammalian cells. It regulates both transcriptional activation and repression, in a seemingly context-dependent manner. YY1 has a well-established role in the development of the central nervous system, where it is involved in neurogenesis and maintenance of homeostasis in the developing brain. In neurodevelopmental and neurodegenerative disease, the crucial role of YY1 in cellular processes in the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 93 publications
3
83
0
Order By: Relevance
“…Although the role of YY1 in gene regulation has been widely studied, the mechanism of YY1 action on tumour growth is distinct in different cancers 40 . Some studies have shown that YY1 mainly acts as a tumour suppressor in pancreatic cancer, 41,42 however, most studies have shown that YY1 exists as a oncogene, such as in gastric cancer and lung cancer 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of YY1 in gene regulation has been widely studied, the mechanism of YY1 action on tumour growth is distinct in different cancers 40 . Some studies have shown that YY1 mainly acts as a tumour suppressor in pancreatic cancer, 41,42 however, most studies have shown that YY1 exists as a oncogene, such as in gastric cancer and lung cancer 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…When the structure of the repressor domain changes and its repression activity is lost. In the cell, YY1 can be transformed into an activating factor only after the N-terminal activation domain is unmasked and exposed under certain conditions [46][47][48][49] . Consistent with our conjecture, the lactylation of the lysine at position YY1 183 may cause the inhibition mechanism to fail and activate the transcriptional activity of YY1, but this hypothesis still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, transcription factor YY1 (Yin Yang 1) is able to act as both a transcriptional activator and repressor, which depend on various post-translational modifications of YY1 and different co-factors binding with YY1 [ 38 , 39 , 40 ]. YY1 plays important roles in neuroprotective pathways associated with ischemic damage, Parkinson’s and Alzheimer’s disease, and acts as a tumor suppressor or stimulator [ 38 , 41 ]. Thus, whether and how PACRG interplays with these transcription regulators and transcription factors, such as YY1, would be attractive research topics.…”
Section: Discussionmentioning
confidence: 99%